2023
DOI: 10.1029/2022ja031181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solar Wind Dynamic Pressure on Distribution of Whistler Mode Waves Based on Van Allen Probe Observations

Abstract: In this study, the effect of solar wind dynamic pressure (PSW) on the global distribution of whistler mode waves (including chorus and hiss waves) while the absence of substorm activity is investigated using the data originating from the Van Allen Probes for nearly 5 years. After the effect of substorm activity is excluded, our statistical results indicate that the hiss and chorus waves exhibit different characteristics with the increase of PSW. The amplitudes of chorus waves increase on the dayside with the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
1
1
0
Order By: Relevance
“…In contrast, plasmaspheric hiss mainly disappeared/weakened on the dayside and intensified on the nightside, which cannot be explained solely by the variations of source chorus. Such different dependences of chorus and plasmaspheric hiss on the solar wind dynamic pressure have also been reported recently by Tang et al (2023). Through simple ray tracing modeling, Yue et al (2017) found that a more stretched magnetic field configuration on the nightside caused by shock compression favors the entry of chorus waves with more fieldaligned wave normal into the plasmasphere, which are generally the majority of observed chorus waves in the equatorial region (Burton and Holzer, 1974;Goldstein and Tsurutani, 1984;Santolík et al, 2014a;Santolík et al, 2014b;Hartley et al, 2019).…”
Section: Prompt Responses Of Plasmaspheric Hisssupporting
confidence: 67%
“…In contrast, plasmaspheric hiss mainly disappeared/weakened on the dayside and intensified on the nightside, which cannot be explained solely by the variations of source chorus. Such different dependences of chorus and plasmaspheric hiss on the solar wind dynamic pressure have also been reported recently by Tang et al (2023). Through simple ray tracing modeling, Yue et al (2017) found that a more stretched magnetic field configuration on the nightside caused by shock compression favors the entry of chorus waves with more fieldaligned wave normal into the plasmasphere, which are generally the majority of observed chorus waves in the equatorial region (Burton and Holzer, 1974;Goldstein and Tsurutani, 1984;Santolík et al, 2014a;Santolík et al, 2014b;Hartley et al, 2019).…”
Section: Prompt Responses Of Plasmaspheric Hisssupporting
confidence: 67%
“…under Different P sw Levels Solar wind dynamic pressure, P sw , is known to be an important parameter impacting the transmission of energy within the magnetosphere and the configuration of its magnetic field. To quantitatively assess the impact of P sw on whistlermode waves in dayside terrestrial space, we first sort the P sw into three levels based on the variations in solar wind dynamic pressure (Tang et al 2023): (a) weak: P sw 1.5 nPa; (b) moderate: 1.5 nPa <P sw < 3 nPa; and (c) strong: P sw 3 nPa.…”
Section: Occurrence and Characteristics Of Whistler-mode Wavesmentioning
confidence: 99%